Fear of Falling and Its Related Factors in the Older Adults with Heart Failure - Seyede Fatemeh Gheiasi; Marzieh Beik Verdi; Farshad Sharifi; Hossein Navid; Masoumeh Zakeri Moghaddam; Elham Navab (Mashhad University of Medical Sciences, 2021)
Fear of falling (FOF) acts as an inhibitory factor for the activities of daily living and causes disability and dependence in the elderly suffering from heart failure (HF). This study aimed to determine FOF among the elderly with HF and its related factors. This cross-sectional study was performed on 445 elderly patients with heart failure who were referred to the HF clinic of Tehran Heart Center affiliated with Tehran University of Medical Sciences, Tehran, Iran, from March to July 2018. Participants in this study were selected randomly. Data collection was conducted using demographic characteristics form and Falls Efficacy Scale-International questionnaires. Data were analyzed using STATA software (Version 14). The mean FOF among participants was 36.7 out of 64 scores (ST=0.27 and CI: 95%). The level of FOF was moderate in 61% of the participants. Based on the obtained results, FOF had no statistically significant correlation with gender, education, smoking, and marital status (P>0.05); however, it had a statistically significant correlation with age, HF class, residence, medications, and the history of falls (P<0.05). It is recommended that health caregivers should develop a comprehensive care program that takes into account such factors as age, HF class, residence, medications, and history of falls to prevent and reduce the FOF. Therefore, given the importance of the issue of FOF in older adults with HF, a comprehensive care program and educational, counseling, and welfare interventions should be developed in a way to prevent and reduce FOF.